2020
DOI: 10.1186/s42523-020-00056-2
|View full text |Cite
|
Sign up to set email alerts
|

Bugs and drugs: a systems biology approach to characterising the effect of moxidectin on the horse’s faecal microbiome

Abstract: Background Anthelmintic treatment is a risk factor for intestinal disease in the horse, known as colic. However the mechanisms involved in the onset of disease post anthelmintic treatment are unknown. The interaction between anthelmintic drugs and the gut microbiota may be associated with this observed increase in risk of colic. Little is known about the interaction between gut microbiota and anthelmintics and how treatment may alter microbiome function. The objectives of this study were: To characterise (1) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 61 publications
4
21
0
1
Order By: Relevance
“…We previously highlighted that susceptible ponies had lower monocyte but higher lymphocyte counts than resistant individuals upon natural strongylid infection 34 . More susceptible individuals also exhibited differential modulation of their faecal microbiota, including enrichment for the Ruminococcus genus 34 , corroborating independent observations of alterations in the gut microbiota composition of infected horses 34 37 .…”
Section: Introductionsupporting
confidence: 80%
“…We previously highlighted that susceptible ponies had lower monocyte but higher lymphocyte counts than resistant individuals upon natural strongylid infection 34 . More susceptible individuals also exhibited differential modulation of their faecal microbiota, including enrichment for the Ruminococcus genus 34 , corroborating independent observations of alterations in the gut microbiota composition of infected horses 34 37 .…”
Section: Introductionsupporting
confidence: 80%
“…We previously highlighted that susceptible ponies had lower monocyte but higher lymphocyte counts than resistant individuals upon natural strongylid infection 25 . More susceptible individuals also exhibited differential modulation of their faecal microbiota, including enrichment for the Ruminococcus genera 25 , corroborating independent observations of alterations in the gut microbiota composition of infected horses [25][26][27][28] .…”
Section: Introductionsupporting
confidence: 79%
“…Peachey et al ( 25 ) confirmed again that anthelmintic treatment was associated with alteration of the relative abundances of the bacterial community. Daniels et al ( 26 ) observed that anthelmintic treatment increased the relative abundances of Deferribacter spp. and Spirochaetes spp.…”
Section: Introductionmentioning
confidence: 99%